Dampak Bencana Terhadap Wilayah Pesisir: Belajar dari Tsunami Aceh - Rosyidie, Arief (Journal of Regional and City Planning, 2006)
Coastal areas have various natural resources potency that can be useful for various activities or land uses. For years, many cities and growth center have been developed in coastal areas. Besides its potency and opportunity for development, some coastal areas are located at hazards areas that can trigger a disaster particularly a tsunami. The impact of disaster (tsunami) to coastal areas is influenced by hazard characteristic, vulnerability, and capcity of the areas. Tsunami that was triggered by strong earthquake in Indian Ocean at December 2004 had caused a huge impact to the coastal areas which covered a serious damage in coastal ecosystem, devastation of housings and other buildings, fish pounds and agricultural areas, local and regional infrastructures, social facilities, economy, pollution of surface water, tsunami waste, etc. The areas also suffer social impact such as interruption of education process, and disease endemics because of poor sanitation condition and health services, as well as psychological disorder (trauma, stress) among Aceh population and their families. Program to rebuild Aceh have been done by BRR (Reconstruction and Rehabilitation Agency) supported by any other institutions, government as well as privates institutions, from local, regional/national and international.